Quaternary Ammonium “Tannate” for Antifouling Coatings - Bellotti, Natalia (2012)
The undesirable accumulation of a wide variety of marine organisms (biofouling) on ship hulls can lead to significantly increased costs, principally by increased fuel consumption to maintain cruising speed. Generally, these coatings have bioactive compounds, called biocides. In this sense, this paper deals with the assessment of the antifouling properties of a natural product derivative obtained from "quebracho" tannin and a quaternary ammonium salt (hexadecyltrimethylammonium bromide ([CH3(CH2)15N(CH3)3]Br). Two derivatives were obtained depending on the precipitation pH (4 and 8). The bioactivity of these derivatives was assessed by means of the Artemia test. Furthermore, soluble matrix paints were prepared with two different binders: rosin/oleic acid and rosin/styrene-acrylate copolymer. The leaching of "quebracho" tannin derivatives from coatings in artificial seawater was monitored until constant values were obtained, previous to the immersion in natural environments. Finally, the antifouling activity of coatings pigmented with the "quebracho" tannin derivative was evaluated in Mar del Plata harbor (38°08′17″S-57 31′18″W). The coating obtained with the derivative obtained at pH 4 and rosin/oleic acid as binder proved to have an acceptable efficiency for 10 months.